2021
DOI: 10.1007/s00125-021-05407-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ertugliflozin on kidney composite outcomes, renal function and albuminuria in patients with type 2 diabetes mellitus: an analysis from the randomised VERTIS CV trial

Abstract: Aims/hypothesis In previous work, we reported the HR for the risk (95% CI) of the secondary kidney composite endpoint (time to first event of doubling of serum creatinine from baseline, renal dialysis/transplant or renal death) with ertugliflozin compared with placebo as 0.81 (0.63, 1.04). The effect of ertugliflozin on exploratory kidney-related outcomes was evaluated using data from the eValuation of ERTugliflozin effIcacy and Safety CardioVascular outcomes (VERTIS CV) trial (NCT01986881). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(167 citation statements)
references
References 30 publications
6
124
2
8
Order By: Relevance
“…28,29 The results of this substudy have the potential to be clinically impactful in that benefits were readily and safely achieved in a population that is typically difficult to manage in clinical practice (ie, patients with long-standing T2DM and established ASCVD inadequately controlled on insulin therapy). The benefits of improved glycaemic control and reduction of BW and SBP observed with ertugliflozin, together with the potential reduction in the risk for hospitalization for heart failure 13,14 and renal outcomes 13,15 observed with ertugliflozin compared with placebo in the overall VERTIS CV study, 13 could alter disease outcome in this important population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 The results of this substudy have the potential to be clinically impactful in that benefits were readily and safely achieved in a population that is typically difficult to manage in clinical practice (ie, patients with long-standing T2DM and established ASCVD inadequately controlled on insulin therapy). The benefits of improved glycaemic control and reduction of BW and SBP observed with ertugliflozin, together with the potential reduction in the risk for hospitalization for heart failure 13,14 and renal outcomes 13,15 observed with ertugliflozin compared with placebo in the overall VERTIS CV study, 13 could alter disease outcome in this important population.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] The effects of the SGLT2 inhibitor ertugliflozin on cardiorenal outcomes in patients with T2DM and established atherosclerotic cardiovascular disease (ASCVD) have been assessed in the VERTIS (eValuation of ERTugliflozin effIcacy and Safety) CV study. [13][14][15] In VERTIS CV, approximately 50% of patients were taking insulin at baseline and, in other SGLT2 inhibitor CV outcome studies, 40% to 50% of patients were on insulin at baseline. [7][8][9]13 Those percentages suggest that substantial numbers of patients with T2DM with or at high risk of ASCVD and kidney events who are using insulin in real-world clinical settings may need additional glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the key composite kidney endpoint, which used "doubling of serum creatinine" for the definition of significant kidney function loss, the impact of ertugliflozin was neutral [41]. However, as presented at the European Association for the Study of Diabetes 2020, with a more modest kidney endpoint comprised of a sustained 40% eGFR decline, a HR of 0.66 was observed (95% CI, 0.50 to 0.88) [42]. Additionally, when stratified by kidney risk in VERTIS-CV as determined by KDIGO risk categories, significant reductions in the HHF/CV death composite were observed in the moderate and high/very high risk categories (P=0.03 for interaction) [43].…”
Section: Sglt2 Inhibition and Clinical Heart And Kidney Protectionmentioning
confidence: 99%
“…These data are in contrast with those obtained in other trials with SGLT2is, although the population of patients with atherosclerotic cardiovascular disease enrolled in VERTIS-CV study was broadly similar to those of previous trials performed with other SGLT2is. However, recently, has been demonstrated that when used in addition to standard of care medications, ertugliflozin is associated with a decrease in the risk of a sustained 40% decline in eGFR, with preservation of eGFR over time and a reduction of UACR in individuals with established atherosclerotic CVD and type 2 diabetes (121).…”
Section: Ertugliflozinmentioning
confidence: 99%